The Nordic Model in Education: Education as part of the political system in the last 50 years - Telhaug, Alfred Oftedal; Mediås, Odd Asbjørn; Aasen, Petter (Scandinavian Journal of Educational Research, 2006)
This article describes, analyses and discusses the development of the Nordic school model in three phases of the post-war period, viewed in the light of the development of the political system throughout the period and in comparison with the development of the school system in the western world in this period. The ?classical period? from 1945 until about 1970 is often referred to as the golden era of social democracy, during which a number of special characteristics were attributed to the model. First, the reforms were introduced on the basis of national policies drawn up by a strong and innovative state in association with business organisations and industry. The main objective was to involve the school in the realisation of social goals such as equal opportunity and community fellowship. School development is very largely determined by state-managed conditions??input management?. The Nordic model was regarded as an ideal for school development in western countries. The Nordic countries generally followed the same course, but at different tempos, with Sweden being the main source of inspiration. During the next phase, 1970-1980/85, the Nordic model was influenced by international, political new radicalism in which increasing importance was attached to pupils' individual emancipation, and there was greater local influence over school development as well as by the teaching profession. In the third and final phase, the Nordic school model was of less importance in comparison to other countries. Partly as a result of new globalisation and free markets, economic competition between nations gained greater influence over school philosophy and development. Technical and instrumental goals were prioritised at the expense of national and social unity. Evaluation of pupils' academic skills was intensified and became an important management tool??output management?. State control diminished as a result of the decentralisation of power and of the increasing influence of international reports and resolutions on school reform in the Nordic countries. During the latter phase the dominant neo-liberal education policy has been subjected to criticism from the culture conservative and social democratic/progressive side.
Keywords: gestion d'établissement scolaire; politique éducative; utilisation des recherches; éducation comparée; éducation prioritaire